Studies on Chemically Modified Fibrinogen - Kloczewiak, M; Wegrzynowicz, Z; Matthias, F.R; Heene, D.L; Zajdel, Maria (Thrombosis and Haemostasis, 1976)
Treatment of fibrinogen with maleic acid anhydride renders fibrinogen unclottable depending on the degree of modification of the molecule. According to radioactive studies the release of fibrinopeptides by thrombin or reptilase is undisturbed. The incoagulability is due to inhibition of the polymerization process of fibrinmonomers derived from modified fibrinogen, mainly caused by the increase of electronegative charges upon the fibrinogen molecule. According to discelectrophoretic analysis modified fibrinogen fails to produce fragments D and E following plasmic digestion, however, may be degraded to high molecular weight products. Modified fibrinogen reveals some similarities to abnormal fibrinogens in congenital dysfibrinogenemia with regard to its functional properties.